Mouse models of preterm birth: suggested assessment and reporting guidelines. Issue 5 (3rd May 2018) - McCarthy, Ronald; Martin-Fairey, Carmel; Sojka, Dorothy K; Herzog, Erik D; Jungheim, Emily S; Stout, Molly J; Fay, Justin C; Mahendroo, Mala; Reese, Jeff; Herington, Jennifer L; Plosa, Erin J; Shelton, Elaine L; et al.
Abstract: Preterm birth affects approximately 1 out of every 10 births in the United States, leading to high rates of mortality and long-term negative health consequences. To investigate the mechanisms leading to preterm birth so as to develop prevention strategies, researchers have developed numerous mouse models of preterm birth. However, the lack of standard definitions for preterm birth in mice limits our field's ability to compare models and make inferences about preterm birth in humans. In this review, we discuss numerous mouse preterm birth models, propose guidelines for experiments and reporting, and suggest markers that can be used to assess whether pups are premature or mature. We argue that adoption of these recommendations will enhance the utility of mice as models for preterm birth. Abstract : To improve reporting of mouse models of preterm birth, a set of universal guidelines and simple assays of developmental markers are proposed to distinguish between mature and premature pups.